Cosmic ray contribution to environmental dose rates with varying overburden thickness - Munyikwa, K. (Ancient TL, 2000)
The dynamic character of most natural depositional systems is such that the cosmic ray dose rate experienced by a buried luminescence dating sample is not static but changes with the fluctuations in the thickness of the overurden. The use of in situ (present day) cosmic ray contribution rates assumes instantaneous deposition of the sedimentary column overlying the sample followed by a period of non-deposition. Where the cosmic ray dose constitutes a major component of the total dose (which may be up to 60%), as is the case with many quartz aeolian dune sand systems, the assumption of instantaneous deposition may introduce notable errors. By reconstructing the burial history of a sample from the top downwards, methodology can be forumlated for estimating the true cosmic ray dose received. Two different scenarios are discussed: i) gradual urail in a single depositional episode and ii) burial by episodic (multiple) increase of overburden.